Evaluating the Impact of Instagram Engagement Metrics on Corporate Revenue Growth: Introducing the Loyalty Rate - Eva Sanches; Célia M.Q. Ramos (Information)
This research explores the impact of social media metrics on revenue growth, specifically focusing on Instagram, a leading platform for businesses to engage consumers and promote offerings. It examines key metrics such as reach, impressions, interaction rate, and virality rate, which gauge user engagement with brand content. A novel metric, the loyalty rate, is introduced, combining interaction and virality rates to measure follower loyalty—those who not only engage but also share content, enhancing organic reach. The methodology involved comprehensive statistical analyses, including descriptive statistics, Pearson’s correlations, and regression models, to investigate the relationship between social media metrics and monthly turnover. The findings reveal a moderate positive correlation between the loyalty rate and turnover, although the statistical significance was insufficient to establish a direct relationship. In contrast, metrics like follower count exhibited a stronger influence on financial performance, indicating that follower growth may be more critical for revenue generation. This study concludes that while engagement and loyalty matter, their effect on turnover is part of a broader digital strategy encompassing various factors beyond direct interactions. Practical recommendations are made for enhancing the loyalty rate and expanding research to include other platforms, like Facebook and LinkedIn, for a more comprehensive understanding of social media’s impact on financial outcomes.